The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1097/nmc.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Care in Women Sent Home in Latent Labor

Abstract: Comfort measures in the birth setting, including in triage, should include a variety of options including ambulation and oral nutrition. Detailed and specific written instructions about early labor and staying comfortable while at home have value for women in this survey regarding their perceptions of care. Results from this survey of low-income women suggest that a subset of women in latent labor just do not want to go home and this may be related to having too much pain and/or travel distance to the hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 1 publication
1
24
0
Order By: Relevance
“…This is in line with results from Carlsson et al [23]. Hosek et al [36] found in their study from low income women who were sent home during latent phase that reasons for wanting to stay at the labour ward were being in pain and/or having a long distance to travel to the hospital. Moore et al [37] found in their study that a barrier to optimal care was lack of informed decision-making.…”
Section: Article In Presssupporting
confidence: 86%
“…This is in line with results from Carlsson et al [23]. Hosek et al [36] found in their study from low income women who were sent home during latent phase that reasons for wanting to stay at the labour ward were being in pain and/or having a long distance to travel to the hospital. Moore et al [37] found in their study that a barrier to optimal care was lack of informed decision-making.…”
Section: Article In Presssupporting
confidence: 86%
“…Providing physical comfort, addressing emotional needs, and ensuring positive patient-health care provider interactions are supportive strategies for women in labor (Bowers, 2002;Paul et al, 2013). Comfort measures and having their concerns heard in a triage environment contributed to women's satisfaction during latent labor (Hosek, Faucher, Lankford, & Alexander, 2014). Simple caring actions, such as providing a pillow or offering a glass of water, contributed significantly to the women's feelings of satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 Furthermore, pregnant women's expectations about labor and their postnatal recall are often incongruent. 14 Collectively, previous studies have described the overall experiences of women in the latent phase of labor prior to hospital admission, 14,17 the experiences and perceptions of women being sent home 16,19 or admitted 20 to the hospital in latent labor, and women's perceptions about their interactions with perinatal health care providers in early labor. 18,21 No studies have specifically examined the decision-making process used by low-risk nulliparous women who decide to stay at home or go to the hospital in early labor in a US maternity care context.…”
Section: Introductionmentioning
confidence: 99%